Moderating variables in the relationship between mental toughness and performance in basketball - Newland, A.; Newton, M.; Finch, L.; Harbke, C. R.; Podlog, L. (Journal of Sport and Health Science, 2013)
Purpose: This study explored the relationship between mental toughness and college basketball performance, specifically examining possible moderating variables (gender and starting status). Methods: Male and female (n ¼ 197) college basketball players completed the Psychological Performance Inventory-Alternative (PPI-A), a measure of characteristics and skills consistent with mental toughness, and the PERF, an objective measure of basketball performance. Results: Findings suggest that basketball performance can be partially predicted by mental toughness and starting status. Males reported greater mental toughness than females. Starters and nonstarters did not differ in mental toughness. Moderated hierarchical regression analysis indicated that mental toughness was related to performance for male players as both a main effect and interaction with starter status. For female players, in contrast, starter status was the only significant predictor of performance. Practitioners are encouraged to foster the psychological skills associated with mental toughness in females and non-starters in basketball. Conclusion: Discussion of the PPI-A as a measure of mental toughness and suggestions for its improvement are explored. A need exists for additional research on mental toughness and objective performance, as performance enhancement is a major impetus for research on mental toughness.